Sobre maldiç\~oes e bênça\~os: É possível gerir recursos naturais de forma sustentável? Uma análise sobre os royalties e as compensaç\~oes financeiras no Brasil - Bruno de Oliveira Cruz; Márcio Bruno Ribeiro (Instituto de Pesquisa Econômica Aplicada (IPEA), 2009)
– This paper analyses risks and opportunities related to the management and the allocation of wealth derived from the exploitation of natural resources in Brazil. We first discuss natural resources curse hypothesis and present some examples to deal with its negative effects based on the international experience. Then, we present the main aspects of legislation which legitimatize wealth from the natural resources exploitation in Brazil. We also examine the actual distribution of wealth derived from petroleum exploitation, showing wealth concentration in some states and municipalities. Finally, we present the more recent proposals for changing Brazilian legislation about distribution of wealth derived from natural resources exploitation.
Keywords: H27; Q32; 330